Perception-Cognition Interface and Cross-Modal Experiences: Insights into Unified Consciousness - Aleksandra Mroczko-Wasowicz (Frontiers Research Topics, 2017)
The present Research Topic explores closely related aspects of mental functioning, namely an interplay between perception and cognition, interactions among various sensory modalities, and finally, more or less unified conscious experiences arising in the context of these relations. Contributions emphasize a high flexibility observed in perception and may be seen as potential challenges to the traditional modular architecture of perceptual systems. Although the articles describe different phenomena, they follow one common theme - to investigate broadly understood unified experience - by studying either perception-cognition integration or the integration between sensory modalities. These integrative processes may well apply to subpersonal unconscious representations. However, the aim here is to approach phenomenal experience and thus a straightforward way of thinking about it is in terms of conscious perception. Putting together scientific and philosophical concerns, this special issue encourages extending the study of perceptual experience beyond the single sense perception to advance our understanding of the complex interdependencies between different sensory modalities, other mental domains, and various kinds of unifying relations within conscious experience. It exhibits a remarkable need to study these phenomena in tangent, and so, the authors examine a variety of ways in which our perceptual experiences may be cross-modal or multisensory, integrated, embodied, synesthetic, cognitively penetrated, or otherwise affected by top-down influences. The Research Topic comprises theoretical and empirical contributions of such fields as philosophy of mind, cognitive science, psychology, and neuroscience in the form of hypothesis and theory articles, original research articles, opinion papers, reviews, and commentaries.The present Research Topic explores closely related aspects of mental functioning, namely an interplay between perception and cognition, interactions among various sensory modalities, and finally, more or less unified conscious experiences arising in the context of these relations. Contributions emphasize a high flexibility observed in perception and may be seen as potential challenges to the traditional modular architecture of perceptual systems. Although the articles describe different phenomena, they follow one common theme - to investigate broadly understood unified experience - by studying either perception-cognition integration or the integration between sensory modalities. These integrative processes may well apply to subpersonal unconscious representations. However, the aim here is to approach phenomenal experience and thus a straightforward way of thinking about it is in terms of conscious perception. Putting together scientific and philosophical concerns, this special issue encourages extending the study of perceptual experience beyond the single sense perception to advance our understanding of the complex interdependencies between different sensory modalities, other mental domains, and various kinds of unifying relations within conscious experience. It exhibits a remarkable need to study these phenomena in tangent, and so, the authors examine a variety of ways in which our perceptual experiences may be cross-modal or multisensory, integrated, embodied, synesthetic, cognitively penetrated, or otherwise affected by top-down influences. The Research Topic comprises theoretical and empirical contributions of such fields as philosophy of mind, cognitive science, psychology, and neuroscience in the form of hypothesis and theory articles, original research articles, opinion papers, reviews, and commentaries.